2017
DOI: 10.1002/bdra.23583
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of whole murine embryos reveals metabolic perturbations associated with maternal valproate‐induced neural tube closure defects

Abstract: Background Valproic Acid (VPA) is prescribed therapeutically for multiple conditions, including epilepsy. When taken during pregnancy, VPA is teratogenic, increasing the risk of several birth and developmental defects including neural tube defects (NTDs). The mechanism by which VPA causes NTDs remains controversial and how VPA interacts with folic acid, a vitamin commonly recommended for the prevention of NTDs, remains uncertain. We sought to address both questions by applying untargeted metabolite profiling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Numerous mechanisms have been proposed by which VPA may disrupt NT closure. These include epigenetic dysregulation ( Tung and Winn, 2010 ), inhibition of folate metabolism ( Fathe et al, 2014 , Roy et al, 2008 , Semmler et al, 2017 ), suppression of nitric oxide signalling ( Tiboni et al, 2013 , Tiboni and Ponzano, 2015 ) and increased reactive oxygen species production ( Akimova et al, 2017 , Tung and Winn, 2011 ). In addition, VPA's anti-acetylation effects may disrupt post-translational modifications of other effector proteins including those involved in actin regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mechanisms have been proposed by which VPA may disrupt NT closure. These include epigenetic dysregulation ( Tung and Winn, 2010 ), inhibition of folate metabolism ( Fathe et al, 2014 , Roy et al, 2008 , Semmler et al, 2017 ), suppression of nitric oxide signalling ( Tiboni et al, 2013 , Tiboni and Ponzano, 2015 ) and increased reactive oxygen species production ( Akimova et al, 2017 , Tung and Winn, 2011 ). In addition, VPA's anti-acetylation effects may disrupt post-translational modifications of other effector proteins including those involved in actin regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Welch’s t-tests, assuming unequal variances (p < 0.05), were used for statistical testing of between-group comparisons. Graphical analysis of results and Welch’s t-tests were performed using GraphPad Prism 19 , 21 24 . CLN2 disease classification was performed using the proprietary open-source software Metaboanalyst 4.0 25 .…”
Section: Methodsmentioning
confidence: 99%
“…It is now established that metabolites can be predetermined by adverse conditions before birth during early development and which play an important role in prevention of disease at adult. Several studies had reported the metabolites changes in fetuses and child (Tomiyasu et al, 2013) or rat embryos (Akimova et al, 2017). Sato, Tomonaga, Denbow, and Furuse (2009) reported the changes of amino acids during embryonic development in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%